IDENTIFYING METHODS THAT SERVE TO DEVELOP COMMUNICATION SKILLS IN PRIMARY SCHOOL STUDENTS AND THEIR PRACTICAL USE DURING THE LESSON (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The use of various methods and methods in the formation of communication skills in primary school students and the development of communication culture in primary school students and the role of communication culture in people's lives such thoughts are discussed